Use of flow diverter device in basilar artery for aneurysm treatment: Case series and literature review - Wang, Chuanchuan; Zhu, Deyuan; Xu, Xiaolong; Zhou, Yu; Zhao, Rui; Li, Qiang; Yang, Pengfei; Huang, Qinghai; Xu, Yi; Liu, Jianmin; Fang, Yibin (Frontiers in Neurology, 2022)
Background: Flow diverters (FDs) for the treatment of basilar artery (BA) aneurysms remain controversial. In this study, we report our initial experience of flow diversion for treatment of this pathology. Methods: Consecutive patients with an aneurysm of the BA that was treated by implantation of the FD were included in our retrospective study. Procedural complications, aneurysm occlusion, and functional outcome were evaluated. FD placement in BA for aneurysm treatment reported in the literature was also reviewed and summarized. Results: Sixteen patients with 16 BA aneurysms were treated by FD implantation with (n=8) or without (n=8) adjunctive coiling. The Tubridge was used in 13 (81.3%) and Pipeline in 3 (18.8%) procedures. Average aneurysm size was 15.7 mm. Four aneurysms were located at basilar apex, six at basilar trunk, and six at vertebrobasilar junction. Three patients experienced procedural complications (18.8%), including two ischemic strokes and one hydrocephalus, with resultant mortality in one case (6.3%). Median follow-up was 7.7 months and available for 15 aneurysms. Complete/near-complete occlusion was seen in 13 (86.7%) aneurysms. Conclusion: In our initial experience, flow diversion is feasible and safe in the treatment of BA aneurysms with promising occlusion rates at mid-term follow-up. Larger cohort studies are required to validate these results.